Circulating Levels of Endotrophin Are Prognostic for Long-Term Mortality after AKI. Issue 5 (26th May 2022) - Sparding, Nadja; Rasmussen, Daniel Guldager Kring; Genovese, Federica; Karsdal, Morten Asser; Hornum, Mads; Feldt-Rasmussen, Bo; Packington, Rebecca; Selby, Nicholas M.
Key Points: In patients with AKI, endotrophin can predict long-term mortality and has a stronger association with mortality than eGFR. In patients with AKI, endotrophin can predict kidney disease progression at later time points and is superior to eGFR. Visual Abstract: Abstract : Background: AKI involves a rapid decrease in kidney function that may be associated with structural damage. Early markers predicting AKI are emerging, but tools to assess patients' long-term health risks after AKI are still lacking. Endotrophin (ETP) is a bioactive molecule released during the formation of collagen type VI. We evaluated the potential of circulating ETP as a prognostic biomarker of adverse outcomes after AKI. Methods: We measured ETP in plasma samples collected 1 year after an episode of AKI, using the PRO-C6 ELISA in 801 patients (393 patients with AKI and 408 controls) from the prospective AKI Risk in Derby (ARID) study (ISRCTN25405995), who were then followed until year 3. Kidney disease progression was defined as ≥25% decline in eGFR combined with a decline in CKD stage. Results: ETP levels were significantly higher in the AKI group compared with controls ( P <0.001). In the AKI group, ETP could discriminate patients with kidney disease progression at year 3 (AUC=0.67, P <0.01), whereas eGFR could not (AUC=0.51, P =0.57). In logistic regression including common risk factors, ETP was independently associated with kidney disease progression in patients with AKI (OR=1.10, P <0.01). ETP could discriminate survivors from nonsurvivors at year 3 (AUC=0.64, P <0.01). In a Cox proportional hazards regression for mortality after AKI that included common risk factors, only ETP (HR=1.05; P <0.001) and age (HR=1.06, P <0.01) were retained in the final model. Conclusions: Patients in the AKI group had higher levels of plasma ETP at year 1 as compared with those who had not had AKI. In the AKI group, ETP levels predict kidney disease progression and mortality. Because ETP is a profibrotic molecule, our findings may indicate that ETP identifies patients with active fibrogenesis after AKI, suggestive of long-term renal remodeling, which is associated with patient outcome.